Perfil clínico e genômico de pacientes com Mielofibrose - Nonino, Alexandre (2019)
Myelofibrosis (MF) is the least prevalent of the classical Myeloproliferative Neoplasms (MPNs) and the one with the worst prognosis. It is characterized by clonal hematopoiesis, inflammation caused by elevated circulating cytokine levels, bone marrow stromal changes and myeloid metaplasia, which cause debilitating symptoms, and increased risk for morbidity and mortality due to thrombotic or hemorrhagic events, cytopenias and transformation to acute leukemia. There are scarce data on the clinical and genomic characteristics of Brazilian patients with MF. We evaluated a cohort of patients followed at health services in Distrito Federal – Brazil, from 2013 to 2018, by collecting clinical and laboratory data and by characterization of their mutational profile with MLPA, NGS and Chromosome Microarray. Overall survival was 3 years, which partially reflects the high prevalence of patients with high risk prognostic score. Seventy eight percent of the patients had cooperative mutations in addition to their driver mutation and 84% had chromosomal gains, losses or areas of copy-neutral loss of heterozigosity (CN-LOH). The latter were frequently associated with acquisition of homozygosis of mutated genes. Monoallelic disruption of the tumor suppressor gene RB1 was found in 15%. Among the mutated genes of interest, we found 3 out of 27 patients with mutations in CSF1R, which is rarely reported in MF. The performance of a personalized prognostic system based on 63 clinical and genomic data was superior to the conventional IPSS. We identify opportunities for improvement of medical assistance for Brazilian patients with MF, including better prognostic characterization.